ANALISIS PERSEPSI KONSUMEN DALAM PELAKSANAAN MARKETING MIX PADA HOTEL RESTY MENARA PEKANBARU (KASUS PADA HUNIAN JASA KAMAR) - Helentina "; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at Resty Menara Hotel Pekanbaru. This study aims to analyze how perceptions of consumers in the implementation of the marketing mix at Resty Menara Hotel Pekanbaru (case in occupancy room service).The data used are primary data and secondary data with descriptive analysis method. In this study, the population is around the occupants of the room service was staying at Resty Menara Hotel Pekanbaru. The sampling technique was accidental sampling where is number of samples taken are as many as 99 people.From the research, it is found that the consumer has a pretty good perception is 43.43% on the implementation of the marketing mix that has been done by the Resty Menara Hotel.Keywords: Consumer Perceptions, Mareting Mix, Resty Menara Hotel